Application of new international classification of adult‐onset diabetes in Chinese inpatients with diabetes mellitus. Issue 7 (12th December 2020) - Wang, Weihao; Pei, Xiaobei; Zhang, Lina; Chen, Zhi; Lin, Dong; Duan, Xiaoye; Fan, Jingwen; Pan, Qi; Guo, Lixin
Abstract: Background: To determine whether the new international cluster‐based classification method can be applied to Chinese inpatients with diabetes mellitus (DM). Methods: Adult patients with DM hospitalized in our tertiary care centre from January 2017 to December 2018 were included in the study. K‐means cluster analysis was done in clusters based on glutamic acid decarboxylase antibodies, body mass index, glycosylated haemoglobin, homeostasis model‐assessed beta cell function, insulin resistance index, and age at diagnosis of DM. Chi‐square test was used to analyse inter‐subgroup differences in DM‐related complications and family history of DM. p < 0.05 was considered significant. Results: A total of 1152 inpatients with DM were included in the study. Five subgroups were obtained by cluster analysis with highest proportion of population in mild obesity‐related DM subgroup (34.55%), followed by mild age‐related DM (21.55%), severe insulin deficiency DM (20.51%), severe insulin resistance DM (19.02%), and severe autoimmune DM subgroup (4.36%). The prevalence of diabetic retinopathy, diabetic peripheral vascular disease, diabetic ketosis, coronary heart disease, hypertension, and family history of DM differed significantly among the subgroups ( p < 0.05 for all). Conclusions: This cluster‐based classification could be applied to hospitalized adult patients with DM in China. It might help in strategizing for DM patients, and hence, improve management of DM in these patients.